ANALISIS PERAN INSPEKTORAT UTAMA DALAM PENCEGAHAN FRAUD (STUDI PADA BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA) - Irwan Wicaksono (Master in Accounting Program, 2019)
ABSTRACT In 2017, there were two cases of fraud which involved Supreme Audit Institution’s (BPK) auditors at the Ministry of Village, Disadvantaged Regions Development and Transmigration; and at PT Jasa Marga. These incidences indicate that the roles of BPK’s Inspectorate Office are not yet optimal in preventing fraud. This research aims at obtaining a description and comprehension about the process of fraud prevention conducted by the Inspectorate Office, and to analyze the reasons why fraud cases persist in the process of inspection performed by BPK auditors, despite the many efforts of fraud prevention by the Inspectorate Office.This research was conducted on the Inspectorate Office which is in charge of performing monitoring on the implementation of all BPK employees’ duties and functions. This research uses a qualitative method with a case study approach. The data collection technique used in this research is semi-structured, in-depth interview using an interview guide. Additionally, this research also uses a document review technique on activity performance reports and internal regulations in the BPK.The research results show that the Inspectorate Office has performed the five types of fraud prevention efforts in the BPK, namely prevention, deterrence, disruption, identification, and prosecution. Whereas the persistence of fraud in the process of examination conducted by the BPK is caused by three factors, namely pressure that comes from needs or lifestyle, opportunity which emerges due to weaknesses in the internal control system, and rationalization.